2017
DOI: 10.1515/hf-2016-0184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cationic polyelectrolytes in contact-active antibacterial layer-by-layer functionalization

Abstract: Contact-active surfaces have been created by means of the layer-by-layer (LbL) modification technique, which is based on previous observations that cellulose fibers treated with polyelectrolyte multilayers with polyvinylamine (PVAm) are perfectly protected against bacteria. Several different cationic polyelectrolytes were applied, including PVAm, two different poly(diallyl dimethyl ammonium chloride) polymers and two different poly(allylamine hydrochloride) polymers. The polyelectrolytes were self-organized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…This indicated that in low-nutrient conditions, the polysaccharide-based textile was itself used as a nutrient source for both the Gram-negative and Gram-positive bacteria. A similar phenomena was also observed for cellulosic pulp fibres (Chen et al 2017). Conversely, sample 180COOB24 showed an obvious reduction of both Gram-negative E. coli and Gram-positive S. aureus.…”
Section: Antibacterial Propertysupporting
confidence: 81%
“…This indicated that in low-nutrient conditions, the polysaccharide-based textile was itself used as a nutrient source for both the Gram-negative and Gram-positive bacteria. A similar phenomena was also observed for cellulosic pulp fibres (Chen et al 2017). Conversely, sample 180COOB24 showed an obvious reduction of both Gram-negative E. coli and Gram-positive S. aureus.…”
Section: Antibacterial Propertysupporting
confidence: 81%
“…Our previous works have presented a three-layer polyelectrolyte system of polyvinylamine (PVAm)/poly­(acrylic acid) (PAA)/PVAm, which was adsorbed onto pulp fibers through layer-by-layer (LbL) deposition and showed excellent antibacterial properties which were attributed to the recharging of the fiber surface by the adsorbed polyelectrolytes. , Further investigations showed that more bacteria were adsorbed onto PVAm/PAA/PVAm-modified cellulose fibers when using the cellulose with higher charge density as a result of a 2,2,6,6-tetramethylpiperidine-1-oxyl radical (TEMPO) oxidation of the fibers . It was demonstrated that the adsorption of bacteria increased because of the higher amount of adsorbed PVAm on the fibers, which was considered as a result of a higher positive charge.…”
Section: Introductionmentioning
confidence: 99%
“…Polyvinylamine (PVAm) is a cationic polymer that is used in the paper industry to increase the strength of paper (BASF 2010). PVAm has good antibacterial properties, due to its primary amine groups, and has been used in several studies to create contact-active antibacterial cellulose using Layer-by-Layer (LbL) modification (Chen et al 2017;Henschen et al 2016;Illergård et al 2011Illergård et al , 2015Westman et al 2009). Chitosan is a cationic polysaccharide derived from naturally occurring chitin through deacetylation, and it is used in cosmetic, food and pharmaceutical products because of its antimicrobial properties (Rinaudo 2006;Sebti et al 2005).…”
Section: Introductionmentioning
confidence: 99%